Robert Jenson's Trinitarian reconstitution of metaphysics - Crocker, J (2016)
This thesis provides a critical examination of Robert Jenson’s doctrine of the Trinity, and the ways in which Jenson’s development of this doctrine corrects central aspects of contemporary metaphysics. Jenson's doctrine of the Trinity develops from his belief in the significance of the narrative form of Scripture, and the way in which the Christian Gospel addresses human religiosity. In order to explain this development, the thesis addresses some topics not addressed in scholarship on Jenson, especially his understanding of theological language and his approach to religious epistemology. It also describes the ways in which Jenson's theological project coheres with the task and method of contemporary metaphysics. After describing Jenson's doctrine of the Trinity, the thesis moves on to address substantial critiques from George Hunsinger, David Bentley Hart, and Oliver Crisp. Hunsinger critiques Jenson on the ground of orthodoxy. He claims that Jenson’s views commit him to a number of heresies, both ancient and modern. David Bentley Hart also critiques Jenson for his perceived unorthodoxy, arguing that Jenson makes the world necessary for God, and makes God responsible for evil in a way which is at odds with the Christian faith. Oliver Crisp critiques Jenson's metaphysics on the grounds of coherence. The thesis provides responses to all of these critiques. Following these critiques, the thesis describes the ways in which Jenson’s Trinitarianism reconstitutes certain central aspects of contemporary metaphysics, especially in the philosophy of time and fundamental metaphysics. Jenson argues on Trinitarian grounds that Christians ought to hold something akin to a moving spotlight view of time. He also argues that Christians ought to deny the category of substance and hold 'event' to be the primary category of metaphysics. The thesis also highlights several weaknesses in Jenson's thought: he has no clear epistemology, his response to the problem of evil is inconsistent, and his work on 'being' is misdirected. None of these weaknesses are found to be fatal to Jenson's project, and the thesis offers suggestions for how each in turn could be corrected.